2017
DOI: 10.1093/gerona/glx185
|View full text |Cite
|
Sign up to set email alerts
|

Frailty, Hospitalization, and Mortality in Residential Aged Care

Abstract: Residents with mild/moderate frailty had higher risk of hospitalization and death than nonfrail residents. Residents who were most frail had higher risk of death but lower risk of hospitalization than nonfrail residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…Along with the lack of a universal definition, there is no single method of quantifying frailty . The two most widely used clinical methods are the “frailty phenotype” and the “frailty index” and both approaches are predictive of adverse health outcomes, such as mortality . The frailty phenotype views frailty as a syndrome caused by a downward spiral of energy reserves .…”
Section: Introductionmentioning
confidence: 99%
“…Along with the lack of a universal definition, there is no single method of quantifying frailty . The two most widely used clinical methods are the “frailty phenotype” and the “frailty index” and both approaches are predictive of adverse health outcomes, such as mortality . The frailty phenotype views frailty as a syndrome caused by a downward spiral of energy reserves .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have conclusively demonstrated that frailty is a predictor for many adverse health outcomes, including disability, falls, delirium, hospitalization, and mortality up to 12 years follow up period 6,914 . However, the majority of these previous studies have focused on the association between frailty and mortality among community-dwelling older persons 911 or residents in long-term care settings 12,15 , rather than on those in acute care settings.…”
Section: Introductionmentioning
confidence: 99%
“…Many older people have several coexisting comorbidities/geriatric syndromes, including cardiovascular disease, renal disease, sensory impairments, lower limb pathology, cognitive changes/dementia, some forms of cancer and frailty that individually and collectively affect life expectancy [6][7][8][9]. Frailty predicts admission to a care home and mortality and increases the risk of death [10,11]. Frailty is assessed in various ways, including phenotype and accumulation of deficits.…”
Section: Introductionmentioning
confidence: 99%